The boundaries of central bank independence: Lessons from unconventional times - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2018)
What institutional arrangements for an independent central bank with a price stability mandate promote good policy outcomes when unconventional policies become necessary? Unconventional monetary policy poses challenges. The large scale asset purchases needed to counteract the zero lower bound on nominal interest rates have uncomfortable fiscal and distributional consequences and require central banks to assume greater risks on their balance sheets. Lack of clarity on the precise definition of price stability, coupled with concerns about the legitimacy of large balance sheet expansions, hinders policy: It encourages the central bank to eschew the decisive quantitative easing needed to reflate the economy and instead to accommodate too-low inflation. The experience of the Bank of Japan's encounter with the zero lower bound suggests important benefits from a clear definition of price stability as a symmetric 2% goal for inflation, which the Bank adopted in 2013. – – Wie muss die Unabhängigkeit einer Notenbank, die das Ziel der Preisstabilität verfolgt, gestaltet sein, damit die Geldpolitik auch beim Einsatz unkonventioneller Maßnahmen erfolgreich ist? Athanasios Orphanides analysiert die Maßnahmen der Bank of Japan (BoJ) seit den späten 1990er Jahren und zeigt auf, worauf bei der Formulierung geachtet werden sollte.
urn:nbn:de:hebis:30:3-475982
Keywords: E52; E58; E61; N15; 330; Bank of Japan; Federal Reserve; ECB; zero lower bound; quantitative easing; central bank independence; price stability; inflation target; balance sheet risk